PERAN AKTOR DALAM PENGELOLAAN SAMPAH RUMAH TANGGA DI KOTA PEKANBARU - Khairul Pratama; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Waste production is increasing every day as population increases and people's consumption patterns. The complexity of the waste management problem certainly cannot be solved by the government itself because it takes a relationship or cooperation from all parties in overcoming the waste problem. The thing that must be done to implement waste management to reduce waste is to play a good role for each actor in household waste management in Pekanbaru City. The purpose of this study was to determine and analyze the role of actors in household waste management in Pekanbaru City and to know and analyze what factors are hampering the role of actors in household waste management in Pekanbaru City. The concept of the theory used in this study is the theory of Husnul Yakin. The research method used is the type of qualitative research with case study methods with data collection techniques through interviews, observation, and documentation. The selection of research informants used purposive sampling techniques. The results showed that the role of actors in waste management in Pekanbaru City had not yet run to the maximum there were still many people who littered and disobeyed the rules and the ineffectiveness of each actor carrying out his role. The inhibiting factors of the role of household waste management actors in Pekanbaru City are the role of the community to participate in managing household waste in Pekanbaru City is still lacking, there are still many people who do not care about environmental cleanliness and there are still many who do not want to participate in banks waste, and the lack of socialization given by the public about the importance of waste management and the importance of participating in waste management. Keywords: Actor, Policy and Waste Management